TERAPI MUSIK KLASIK TERHADAP PENURUNAN RASA NYERI PADA PERSALINAN DI KLINIK KASIH IBU DELI TUA SUMATERA UTARA - Modalta Barus (Universitas Negeri Medan, 2013)
This study shows that classical music plays an important role in the birth process in Klinik Kasih Ibu. Where classical music have an impact both on penurunaan pain during childbirth as well as create the impression relaxed, casual, comfortable, tends to make the pulse is constant, giving effect to calm the chaotic mind and excessive fear. From interviews with birth mothers, almost all responses are positive and all mothers love classical music therapeutic use in labor.